Cytokinin Activity in Rose Petals and Its Relation to Senescence - Mayak, S. (1970)
Cytokinin activity in young rose petals was higher than in old ones. The content of endogenous cytokinins in petals of a short-lived variety (Golden Wave) was lower than in a long-lived variety (Lovita). Application of the cytokinin, N(6)-benzyladenine, increased longevity of the short-lived variety. This strengthens the view that cytokinins participate in the endogenous regulation of senescence in rose petals.